Polyphenolic Nutraceuticals to Combat Oxidative Stress Through Microbiota Modulation - Vamanu, Emanuel (Frontiers in Pharmacology, 2019)
Due to their direct relationship with the activity of the gut microbiota, nutraceuticals are, at present, an effective alternative for the mitigation and alleviation of the dysfunctions governed by oxidative stress. The escalation in the number of the target group patients (diabetes, cardiovascular dysfunction, cancer, etc.) has spurred the quest for alternative action methods. The therapeutic value is determined through in vitro and in vivo methods, and involves the analysis of the therapeutic index. As the adverse outcomes are decreased, the pharmacological potential is assessed by the mechanisms, including biotransformation and the identification of the relevant biomarkers. Inflammatory action is among the principal effects that need to be reduced because it favours the presence of free radicals and dysbiosis. This article aimed at highlighting the action of the nutraceuticals in minimising the oxidative stress by directly influencing the microbiota and slowing down the inflammatory progression. The pharmacological aspects as a therapeutic indicator of the use of nutraceuticals in improving the population health..